2019
DOI: 10.3386/w25488
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Affordable Care Act: Evidence from California's Hospital Sector

Abstract: The Affordable Care Act (ACA) authorized the largest expansion of public health insurance in the U.S. since the mid-1960s. We exploit ACA-induced changes in the discontinuity in coverage at age 65 using a regression discontinuity based design to examine effects of the expansion on health insurance coverage, hospital use, and patient health. We then link these changes to effects on hospital finances. We show that a substantial share of the federally-funded Medicaid expansion substituted for existing locally-fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Policies like Medicaid expansion, which promote improved health insurance coverage for previously uninsured people, help reduce uncompensated care expenditures and strengthen hospitals’ financial positions 54,55 . Previous studies have also found that Medicaid expansion is associated with improved hospital financial performance and lower likelihoods of closure 41,47 . Our analysis reinforces those results while demonstrating the compounding nature of the time component.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Policies like Medicaid expansion, which promote improved health insurance coverage for previously uninsured people, help reduce uncompensated care expenditures and strengthen hospitals’ financial positions 54,55 . Previous studies have also found that Medicaid expansion is associated with improved hospital financial performance and lower likelihoods of closure 41,47 . Our analysis reinforces those results while demonstrating the compounding nature of the time component.…”
Section: Discussionsupporting
confidence: 89%
“…Our survival analysis results suggest that the risk of rural hospital closure increases as the levels of community unemployment and uninsurance rise. Recent studies have also found that increases in community unemployment 25,26,34 and uninsurance 41,47 are associated with hospitals’ financial distress and closure, but have stopped short of documenting the time‐relevant associations of these variables. These considerations are important when assessing policies that can help at‐risk hospitals and communities.…”
Section: Discussionmentioning
confidence: 99%
“…Whether hospitals are in rural or urban areas also constitutes a source of heterogeneity. A few single-state studies find that rural areas substantially benefit from Medicaid expansion in early expansion states such as Oregon (Allen et al 2018) and California (Duggan et al 2018). Rural hospitals in Medicaid expansion states might expect greater improvement in their financial outcomes for several reasons.…”
Section: Literature Reviewmentioning
confidence: 99%
“…First, a substantial share (over 20%) of individuals who are eligible for the ACA expansion and the enhanced federal support were previously enrolled in Medicaid at lower federal reimbursement rates (Dorn, Francis, Snyder, & Rudowitz, 2015;Hall, 2018). Second, Medicaid funds may supplant some direct provision of health care services through public clinics, mental health facilities, and public hospitals that require state funding (Duggan, Gupta, & Jackson, 2019). Third, states may be able to reduce direct state spending on health care for individuals involved in the criminal justice system (Levy et al, 2020).…”
Section: Background On Financing Of Medicaidmentioning
confidence: 99%